Study on the transient expression of hemagglutinin antigen of influenza A/H7N9 virus in Nicotiana benthamiana using agro-infiltration - Thủy, Lê Thị; Ngọc, Lê Thu; Thương, Hồ Thị; Ngọc, Phạm Bích; Nhân, Lâm Đại; Hà, Chu Hoàng (Vietnam Journal of Biotechnology, 2018)
Avian influenza A/H7N9 is a subtype of influenza viruses that has been detected in birds in the past. This subtype has not been previously seen in either animals or human until it was found in March 2013 in China. However, since then, infections of modified H7N9 in both human and birds have been observed such as H7N2, H7N3 and H7N5 subtypes. Hemagglutinin (HA) is the most important antigen for induction of immunity, and is a target to develop influenza vaccines. In this study, the gene encoding HA protein was sucessfully inserted into pRTRA vectors to generate 35S-HA-histag-cmyc-ELP-KDEL and 35S-HApII-histag-cmyc-ELP-KDEL cassettes in the absence and presence of trimer motif GCN4, respectively in order to enhance accumulation of recombinant proteins in plants. These cassettes were inserted into pCB301 binary vectors and transformed into Agrobacterium tumefaciens in order to carry out the transient expression in Nicotiana benthamiana leaves. Five days after infiltration, the total soluble protein was extracted and analysed in SDS-PAGE. The HA-ELP and (HApII-ELP)3 recombinant proteins were detected by Western blot using anti-cmyc monoclonal antibody. These results showed that HA protein fused ELP was observed in monomeric and trimeric forms. The plant extract containing hemagglutinin protein in monomeric and trimeric forms were characterized bio-function using hemagglutination assay. The plant extract containing hemagglutinin protein in trimeric form agglutinated chicken red blood cells at concentration of 94 µg protein/ml whereas the plant extract containing hemagglutinin protein in monomeric form did not agglutinate chicken red blood cells at the same of protein concentration.